2012
DOI: 10.1074/jbc.m112.340869
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Efnb1 Protein, a Ligand of Eph Receptor Tyrosine Kinases, in Modulating Blood Pressure

Abstract: Background: Currently, there is no knowledge about the function of ephrins in vascular smooth muscle contraction and blood pressure regulation. Results: Stimulating Efnb1 reduces vascular smooth muscle cell contraction. Efnb1 null mutation increases RhoA activation and heightens blood pressure in mice. Conclusion: Efnb1 can regulate vessel tone and blood pressure. Significance: We identified a new group of molecules capable of regulating blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 38 publications
(43 reference statements)
1
34
1
Order By: Relevance
“…In support of this notion, we have shown that deletion of EFNB1, a ligand of EPHB6, results in a hypertensive phenotype in mice23. Therefore, we identified EPHB6 and, by logical extension and with certain experimental evidence, its ligands (EFNBs) as novel BP regulatory factors in animal models.…”
mentioning
confidence: 53%
See 3 more Smart Citations
“…In support of this notion, we have shown that deletion of EFNB1, a ligand of EPHB6, results in a hypertensive phenotype in mice23. Therefore, we identified EPHB6 and, by logical extension and with certain experimental evidence, its ligands (EFNBs) as novel BP regulatory factors in animal models.…”
mentioning
confidence: 53%
“…Our previous studies2223 along with some of our unpublished observations indicate that molecules in the EPHB and EFNB families ( e.g., EPHB6, EFNB1, EFNB2, and EFNB3) and a certain adaptor protein (GRIP1) within their signalling pathways are novel factors that can modulate BP in mice. The relevance of these molecules in human BP regulation was investigated.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…25,26 In an additional study, we demonstrated that EPHB4 deletion leads to reduced BP. 27 As EFNB2 is the preferred ligand of EPHB4, we thus asked the question whether its deletion in vascular smooth muscle cells (VSMCs) will have a similar BP reduction effect.…”
Section: Introductionmentioning
confidence: 73%